Regulatory Role of Long Noncoding RNAs LINC00449 in Hepatocellular Carcinoma Mechanism and Prognosis Via Sponge miR-329-3p/KIF5A Axis - Tang, Yangyang; Lin, Jinhuang; Chi, Xiaobin; Zhang, Yichuan; Xing, Tonghai (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Hepatocellular carcinoma (HCC) is a globally prevalent malignant tumor with high recurrence and mortality rates. Long noncoding RNAs (lncRNAs) have been utilized to investigate the progression of various cancers, including HCC. The objective of this research is to explore the mechanism and prognostic impact of lncRNA LINC00449 on HCC. Materials and Methods: LINC00449 and miR-329-3p levels in HCC were measured using RT-qPCR. The impact of high- or lowLINC00449 expression on survival was tested. CCK-8, plate cloning, flow cytometry, and Transwell assays were selected to assess the biological functions of HCC cells. Kaplan–Meier and multivariate Cox analyses were conducted to evaluate the potential of LINC00449 as a prognostic marker for HCC. The interaction between LINC00449, miR-329-3p, and KIF5A was investigated through luciferase activity assays. Results: LINC00449 expression in HCC tissues was increased. Silencing of LINC00449 improved the survival prospects of patients with HCC. Moreover, LINC00449 targeting the miR-329-3p/KIF5A axis influences the progression of HCC. Conclusion: LINC00449 may become a biomarker for the prognosis of HCC, and the LINC00449/miR-329-3p/KIF5A regulatory network mediates the deterioration of HCC. Cite this article as: Tang Y, Lin J, Chi X, Zhang Y, Xing T. Regulatory role of lncRNA LINC00449 in hepatocellular carcinoma mechanism and prognosis via sponge miR-329-3p/KIF5A axis. Turk J Gastroenterol. Published online November 4, 2024. doi 10.5152/tjg.2024.24297